Marcos Suzano: inovações técnicas, tecnológicas e influências na performance do pandeiro - Barbosa, Katiusca Lamara dos Santos (2020)
Marcos Suzano is a percussionist, known for his performance with the tambourine. With his innovative technique, he inserted the instrument into various national and international musical contexts. Using technological resources, he developed his own style of playing, and has influenced new tambourine players, expanding the musical contexts in which the tambourine can be inserted. The tambourine is an instrument widely used in Brazil in national genres like samba, choro and others. To carry out this research a survey of literature served to define the concepts and epistemological bases of the work. The theoretical framework was defined using the concepts of ethnomusicology, musicology and sociology. To gather information we carried out field research through interviews and participant observation. Furthermore, audio and video records were used to understand the elements of Marcos Suzano’s performances. After categorizing and analyzing the data, we developed an analytical description of the aspects that characterize the construction process of music making of Marcos Suzano, his interaction with musicians and musical groups; and his influence on the formation of new tambourine players. Furthermore, this study highlights aspects related to the historical and organological significance of the tambourine, and its function within Brazilian popular music.